The Effects of Listening to the Qur'an in the Postoperative Management of the Patients Undergoing Laparoscopic Cholecystectomy in the Day Surgery Unit - Maarof, Siti Rosnah; Che An, Ahmad; Atkins, Leanne; Devol, Edward Bentz; Hussain, Abeer; Khatijah Lim, Abdullah * (Elsevier, 2023)
Purpose: To determine if listening to verses of the Qur'an during the immediate postoperative period has an effect on patients' anxiety levels, the number of opioids used to control pain, and the length of stay (LOS) in the Post Anesthesia Care Unit (PACU).